Improvement of the flooding tolerance in the flowering stage by using foreign genetic resources in soybeans in Hokkaido - Hideki Kurosaki; Yoko Yamashita; Chika Suzuki; Hiroshi Shinada (Plant Production Science, 2025)
Excess soil moisture severely impacts soybean production globally. Global warming has been accompanied by increased precipitation in Hokkaido, and exあcess soil moisture, especially around the flowering stage, severely reduces soybean growth and crop yield. To reduce such damage, it is important to develop flooding-tolerant varieties. We investigated agronomic characteristics related to flooding tolerance in two elite breeding lines (Tokei-1365, Tokei-1414) derived from crosses with the flooding-tolerant cultivar Shokukei-32. The photosynthetic rate did not differ significantly among these materials under a flooding treatment. However, the two elite breeding lines and Shokukei-32 showed significantly milder flooding damage than did the flooding-sensitive variety Toyoharuka. The milder damage was reflected by lower wilt scores, and higher pod number, root weight, and seed yield. It is considered that the two breeding lines genetically gained flooding tolerance from Shokukei-32. The versatility of a previously identified quantitative trait locus related to flooding tolerance (qFTA2–1, detected in a Shokukei-32 × Toyoharuka population) was assessed. The effect of this QTL was not always detected in cross combinations between Shokukei-32 and other parents, but was stably detected in Toyoharuka near-isogenic lines. Therefore, this QTL is effective in a specific genetic background (i.e. Toyoharuka). We assessed the flooding tolerance of new foreign genetic resources that had shown milder damage in preliminary trials. Seven varieties showed similar or milder flooding damage compared with that of Shokukei-32 as measured by the wilt score, root weight, and seed yield. These varieties are considered to be promising flooding-tolerant materials.